Invasive myoepithelial carcinoma ex pleomorphic adenoma of the major salivary gland: two case reports - Wakasaki, Takahiro (BMC Cancer, 2016)
BACKGROUND: Myoepithelial carcinoma (MEC) is a rare salivary gland tumor. Its long-term prognosis remains unknown because of the paucity of reported cases with long-term follow-up. Although some case series exist, the clinical features of MEC vary considerably depending on the site of origin. Therefore, accumulation of these rare cases is important. CASE PRESENTATION: Case 1: An 89-year-old man presented with a 10-year history of a mass originating from the right parotid gland and involving the neck. The mass grew rapidly for 3 months, reaching approximately 8 cm. There was no facial paralysis. MEC ex pleomorphic adenoma (PA) was suspected. Superficial parotid gland resection was performed in 2013; the tumor grade was pT3N0M0, and the resection margins were free of carcinoma. Because of several high-risk factors for metastasis (i.e., invasive carcinoma ex PA, high MIB1 index, and mutant p53 protein positivity), radiotherapy and chemotherapy were recommended as adjuvant therapy. Although the patient refused adjuvant therapy, he was recurrence-free at 36 months after surgery. Case 2: A 54-year-old woman presented with a >10-year history of a right submandibular mass, which grew rapidly for 1 year, reaching approximately 6 cm. Preoperative diagnosis was PA of the right submandibular gland. Submandibular gland resection was performed in 2013. Pathological analysis revealed invasive MEC ex PA, pT3N0M0; in addition, the carcinoma portion had an extra capsule and had invaded the platysma muscle close to the margin. An MIB1 index of 40 % and mutant p53 protein positivity indicated a high risk for metastasis. Additional resection and right neck dissection revealed no residual carcinoma. The patient refused adjuvant chemotherapy. One year after surgery, metastasis to the right pulmonary hilar node and both lungs were detected. Chemotherapy prevented recurrent growth of the lesion and extended survival. The patient was alive with cancer 30 months after the first surgery. CONCLUSIONS: High expression of the Ki67 labeling index might reflect prognosis of these cases. Chemotherapy for distant metastasis was effective, as expected. Further accumulation of cases and long follow-up data are needed to elucidate the pathophysiology and prognosis of MEC ex PA.